The Cloud-to-Thing Continuum: Opportunities and Challenges in Cloud, Fog and Edge Computing - Lynn, Theo; Mooney, John G; Lee, Brian; Endo, Patricia Takako (Palgrave Studies in Digital Business & Enabling Technologies, 2020)
The Internet of Things offers massive societal and economic opportunities whileat the same time significant challenges, not least the delivery and managementof the technical infrastructure underpinning it, the deluge of data generated fromit, ensuring privacy and security, and capturing value from it. This Open Access Pivot explores these challenges, presenting the state of the artand future directions for research but also frameworks for making sense of thiscomplex area. This book provides a variety of perspectives on how technologyinnovations such as fog, edge and dew computing, 5G networks, and distributedintelligence are making us rethink conventional cloud computing to support theInternet of Things. Much of this book focuses on technical aspects of the Internetof Things, however, clear methodologies for mapping the business value of theInternet of Things are still missing. We provide a valuemapping framework forthe Internet of Things to address this gap. While there is much hype about the Internet of Things, we have yet to reach the tipping point. As such, this bookprovides a timely entrée for higher education educators, researchers and students, industry and policy makers on the technologies that promise to reshapehow society interacts and operates.